In Search of Excellence : Lessons from America's Best-run Companies - Peters, Thomas J.; Waterman, Robert H. (Lahore Ferozsons, 1982)
Discusses eight basic practices characteristic of successfully managed companies.
Include Notes and Index
Keywords: Industrial Management -- United States -- Management--Technique -- Organizational Effectiveness -- Total Quality Management